Evaluation of the anti-osteoarthritic effects and mechanisms of Cissus quadrangularis extract containing quercetin and isorhamnetin in a rat model of monosodium iodoacetate-induced osteoarthritis - Yean-Jung Choi; Jae In Jung; Jaewoo Bae; Jae Kyoung Lee; Eun Ji Kim (Food & Nutrition Research)
Background: Osteoarthritis (OA) is a degenerative joint disease characterized by cartilage degradation, subchondral bone erosion, and chronic inflammation. Current treatments primarily focus on symptom relief and have significant side effects, highlighting the need for safer, more effective alternatives. Cissus quadrangularis extract (CQE), containing bioactive flavonoids quercetin and isorhamnetin, has shown potential anti-inflammatory and cartilage-protective properties. Objective: This study aimed to investigate the anti-osteoarthritic effects and mechanisms of action of CQE in a monosodium iodoacetate (MIA)-induced OA rat model. Design: Sprague-Dawley (SD) rats were induced with OA through intra-articular injection of MIA and treated with CQE at doses of 30, 50, and 100 mg/kg body weight (BW)/day. The effects of CQE on knee joint damage, subchondral bone erosion, cartilage structure, proteoglycan content, and the expression of inflammatory mediators and matrix metalloproteinases (MMPs) were assessed using micro-computed tomography (micro-CT), histological staining, immunofluorescence, and real-time reverse transcription-polymerase chain reaction (RT-PCR). Results: CQE significantly mitigated knee joint damage, reduced subchondral bone erosion, and enhanced bone volume and trabecular structure in MIA-induced OA rats. It also preserved cartilage integrity by maintaining proteoglycan content and the expression of collagen type II alpha 1 (COL2A1) and aggrecan. Moreover, CQE suppressed the mRNA expression of inflammatory mediators [inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and 5-lipoxygenase (5-LOX)], pro-inflammatory cytokines [interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α)], and MMPs (MMP-2, MMP-3, MMP-9, and MMP-13), indicating strong anti-inflammatory and cartilage-protective effects. Conclusions: CQE exhibits significant therapeutic potential in managing OA by targeting multiple aspects of disease progression, including inflammation, cartilage degradation, and bone erosion. Further research is needed to explore long-term efficacy, safety, and the molecular mechanisms of CQE, as well as to validate these findings in human clinical trials.